A Review on Crypto Currency with Distributed Ledger Technology for Blockchain Technology - et. al., Dr. M. Z. Shaikh , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper conducted a detailed examination of blockchain-based technology across a wide range of fields. The objective is to discover the current state of blockchain technology and its applications, as well as how certain facets of this innovative technology can change conventional business practises. Multiple academic papers published in high-ranking scientific journals have theoretical background. As a way of streamlining our assessment and documenting the constantly evolving blockchain domain, this study includes publications from the last decade as well as several reports from the literature. Based on a detailed, systematic review and thematic content analysis of the discovered literature, we present a comprehensive classification of blockchain allowed applications across various industries. We also address the exposure found in the related literature, specifically the limitations of blockchain technology and how these limitations manifest themselves across various sectors and industries. We recognize numerous research gaps and potential exploratory directions based on these results, which are expected to be of great benefit to both academics and practitioners. The race toward trustworthy distributed networks has generated a lot of interest recently, thanks to developments in cryptocurrency platforms like Bitcoin. Multiple Distributed Ledger Technologies (DLTs) are fighting right now to show off their skills and how they might overcome the shortcomings of others. Both distributed ledger systems rely on a distributed, open peer-to-peer network and a set of modular frameworks, such as cryptographic hashes and consensus mechanisms. As a common denominator, all distributed ledger systems depend on a shared, distributed peer-to-peer network and a set of modular structures such as cryptographic hashes and consensus mechanisms. However, their implementations vary greatly in terms of data structure, error tolerance, and consensus approaches. In terms of cost, protection, latency, and efficiency, this divergence affects the design of each DLT case. We present four current DLT implementations in this paper. Each technology's characteristics are discussed, as well as a preliminary comparison.